Improved isotopic model based on 15N tracing and Rayleigh‐type isotope fractionation for simulating differential sources of N2O emissions in a clay grassland soil. (15th February 2019) - Castellano‐Hinojosa, Antonio; Loick, Nadine; Dixon, Elizabeth; Matthews, G. Peter; Lewicka‐Szczebak, Dominika; Well, Reinhard; Bol, Roland; Charteris, Alice; Cardenas, Laura
Abstract : Rationale: Isotopic signatures of N2 O can help distinguish between two sources (fertiliser N or endogenous soil N) of N2 O emissions. The contribution of each source to N2 O emissions after N‐application is difficult to determine. Here, isotopologue signatures of emitted N2 O are used in an improved isotopic model based on Rayleigh‐type equations. Methods: The effects of a partial (33% of surface area, treatment 1c) or total (100% of surface area, treatment 3c) dispersal of N and C on gaseous emissions from denitrification were measured in a laboratory incubation system (DENIS) allowing simultaneous measurements of NO, N2 O, N2 and CO2 over a 12‐day incubation period. To determine the source of N2 O emissions those results were combined with both the isotope ratio mass spectrometry analysis of the isotopocules of emitted N2 O and those from the 15 N‐tracing technique. Results: The spatial dispersal of N and C significantly affected the quantity, but not the timing, of gas fluxes. Cumulative emissions are larger for treatment 3c than treatment 1c. The 15 N‐enrichment analysis shows that initially ~70% of the emitted N2 O derived from the applied amendment followed by a constant decrease. The decrease in contribution of the fertiliser N‐pool after an initial increase is sooner and larger for treatment 1c. The Rayleigh‐type model applied to N2 O isotopocules data (δ 15 N bulk ‐N2 O values) shows poor agreement with the measurements for the original one‐pool model for treatment 1c; the two‐pool models gives better results when using a third‐order polynomial equation. In contrast, in treatment 3c little difference is observed between the two modelling approaches. Conclusions: The importance of N2 O emissions from different N‐pools in soil for the interpretation of N2 O isotopocules data was demonstrated using a Rayleigh‐type model. Earlier statements concerning exponential increase in native soil nitrate pool activity highlighted in previous studies should be replaced with a polynomial increase with dependency on both N‐pool sizes.